Implementation of Character Education Values in Children’s Song Literature in Rokan Hulu, Riau Regency - Arianti, Rita; Fitrah, Yundi; Nazurty, Nazurty; Kusmana, Ade; Nuratika, Nuratika (PPSDP International Journal of Education, 2023)
The background of this research is the younger generation, especially students in this digital era, have been heavily influenced by foreign cultures so that the nation’s character has declined. This needs to get the attention of parents and educators in strengthening the character education values ​​of students. These character education values ​​can also be guided by the values ​​contained in the oral literature of children’s songs. Character education values ​​in children’s songs can be implemented in learning literature at school. This type of research is a literature review, namely the process of placing, obtaining, reading, and evaluating research literature related to the researcher’s interest. The benefit of this research is the implementation of character education values ​​in oral literature of children’s songs. The result of this research is a literature study which obtained 10 articles according to the values ​​of character education in accordance with a review of articles regarding the values ​​of character education. Novelty in this study is the values ​​of character education in children’s songs that are applied in learning literature in junior high schools (SMP).